(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
Learning a new language brings challenges for students. One of these challenges has to do with the communicative factor since this factor is necessary within an environment and a context, to receive and transmit information. Thus, in the following research, a didactic strategy was designed to improve the ability of EFL students to listen in English at the Escuela de Idiomas y Dialectos del Ejército (ESIDE). This research is categorized as a mixed type, with a quasi-experimental design and its objective was to determine the level of listening skills that students had when they entered the course, to apply the didactic strategy, and to evaluate how this strategy favored the development of the communicative factor. The didactic strategy was applied virtually once a week for six weeks and focused on improving pragmatics, intonation, and accents. The obtained results during the research have shown the progressive improvement in pragmatics, understanding, and intonation in the students reflected when starting and developing a basic conversation without the need to resort to translators or other tools. Besides, it was evidenced that alternative, novel methods mediated by new technologies appear to be equally or more effective. Even, it is highlighted that better learning of English is perceived using remote strategies than face-to-face ones.